PENDIDIKAN ISLAM DAN PENGEMBANGAN KESADARAN LINGKUNGAN - Sabri Sabri (FORUM PAEDAGOGIK, 2021)
The methodology used in this research is qualitative using descriptive method. Data collection techniques are observation, interviews and documentation. The data analysis management technique went throught three stages, namely data reduction, data presentation, and conclution drawing, and data validy assurance techniques were participation extension, observation persistenceand triangulation.The results showed that the teacher’s role in fostering the character of students, especially PAI teacher’s at Sekolah Dasar Islam Terpadu Darul Hasan Padangsidimpuan was to provide good guidance and directions to students, to set themselves as good role models so that students get good feedback in everyday life, provide real examples both during and outside of leaning, and function as an advisor for children because the main function of a teacher is not only to transfer of knowladge but also to strive for students to have faith, morals and noble character towards Allah SWT such as praying before and after studying, praying duha in congregation, praying dzuhur in congregation, memorizing short suras, hadist, and daily prayers. Then the second, character towards oneself includes honestly, discipline, and manners. And the factor that becomes an obstacle in character building in this school is the family factor, namely parants, self and environmental factors.